Is the expression of matrix metalloproteinases (MMP-2, -9) and tissue inhibitors of metalloproteinases (TIMP-1, -2, and -3) associated with angiogenesis and clinicopathological features for breast cancer? (Journal of Health Sciences, 2017)
Introduction: Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are involved in the progression of several tumors, including breast cancer. Our aim was to investigate the association of immunohistochemical expression of protein MMP-2, and -9 and tissue inhibitors TIMP-1,-2,-3 by tumoral cells in the process of angiogenesis and to define their relation with clinicopathological features for breast cancer.Methods: Immunohistochemical analysis of MMP-2,-9, TIMP-1,-2,-3, endoglin/CD105, estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status was performed on 79 tissue samples of breast cancer with axillary lymph node dissection.Results: Statistically significant difference was found between mean age of patients and tissue inhibitors of metalloproteinase (TIMP-1) expression status (p=0.008), i.e., women with TIMP-1 negative tumors were on average younger (mean age 46.5) compared to women with TIMP-1 positive tumors (mean age 58.1); TIMP-2 expression status showed association with ER status (p=0.017), while TIMP-3 negative tumors were on average more frequently ER and PR negative (p=0.016; p=0.027). Status of protein expression of MMP-9 was associated with TIMP-1 protein expression status (p=0.033), i.e., breast cancers with overexpression of protein MMP-9 were more frequently TIMP-1 protein positive.Conclusion: Only TIMPs were associated with clinicopathological features for breast cancer. TIMP-2 expression was associated with worse (TIMP-2 positive tumors were frequently ER-negative), while TIMP-3 expression in tumoral cells was associated with better clinicopathological features for breast cancer (TIMP-3 positive tumors were frequently ER and PR positive).